1993
DOI: 10.1021/bi00057a034
|View full text |Cite
|
Sign up to set email alerts
|

The antitumor drug nogalamycin forms two different intercalation complexes with d(GCGT).cntdot.d(ACGC)

Abstract: The structures of the physical complex of d(GCGT).d(ACGC) with the anthracycline antitumor drug nogalamycin were studied in order to determine the sequence specificity and the drug orientation at the symmetric d(C2G3).d(C6G7) binding site of this oligonucleotide. For this purpose, one- and two-dimensional NMR techniques were used in combination with molecular mechanics and molecular dynamics computations. Analysis of the NMR spectra reveals that nogalamycin forms two different intercalation complexes with d(GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…1). One of the sugars must project into the major groove of the double helix while the other occludes the minor groove (Fox and Waring, 1986;Egli et al, 1991 ; van Houte et al, 1993). The tracks on the left-hand side of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). One of the sugars must project into the major groove of the double helix while the other occludes the minor groove (Fox and Waring, 1986;Egli et al, 1991 ; van Houte et al, 1993). The tracks on the left-hand side of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It does not follow that drugs will consistently adopt a common mode of interaction at all possible sites, as Fox and Waring (1986) were forced to conclude in respect of the orientation of nogalamycin bound to DNA and others have since clarified (Searle et al, 1988;Egli et al, 1991 ;van Houte et al, Definitive evidence for bis-intercalation via the major groove of the helix will have to await the determination of a high-resolution structure for an oligonucleotidehis-naphthalimide complex by NMR or X-ray crystallography, as has been achieved for ditercalinium (Williams and Gao, 1992). Efforts to obtain structural data by these means are under way.…”
Section: Discussionmentioning
confidence: 99%
“…DNA footprinting studies have indicated preferential binding at d(CA)⅐d(TG) steps (4). NMR studies using nuclear Overhauser effect data have confirmed that sequences containing more than one potential site can form two different intercalation complexes with roughly equal proportions (5). The x-ray structures of the DNA complexes with nogalamycin and with daunomycin and adriamycin, other anthracycline antibiotics with anti-tumor activities and similar sequence preferences, have utilized modifications to the hexameric sequence d(CGTACG).…”
mentioning
confidence: 98%
“…As shown in Figure 1, the aglycon ring of nogalamycin intercalates into DNA base pairs while the nogalose and bicyclic amino sugars are positioned in the minor and major grooves of DNA, respectively. Unlike other DNA minor groove binders, such as Ho33342, distamycin and netropsin, which prefer binding to AT-rich DNA (28), nogalamycin prefers binding to GC base pairs (27). However, because of the hook-like structure of intercalated nogalamycin, transient local melting of DNA has been proposed to facilitate nogalamycin binding to the GC base (24,29).…”
mentioning
confidence: 99%